2021
DOI: 10.2147/ijgm.s303717
|View full text |Cite
|
Sign up to set email alerts
|

Association Between PDL1 Genetic Variation and Efficacy of Apatinib Monotherapy in Patients with Previously Treated Advanced NSCLC: A Real-World Retrospective Study

Abstract: Background This study aimed to explore associations between PDL1 polymorphisms and efficacy of apatinib for patients with previously treated advanced non–small cell lung cancer (NSCLC) in a real-world setting. Methods We retrospectively recruited 148 patients with previously treated advanced NSCLC from January 2015 to December 2019 continuously. Clinical efficacy in patients receiving apatinib treatment was evaluated. Adverse reactions were do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…To our knowledge, management of the patients and adherence of the therapy in a retrospective study was not sufficient and normative compared with the well-designed phase III clinical trial, which was proved in another retrospective study. 28 A third reason could be attributed to the fact that patients with ECOG 2 score in our study accounted for a much higher proportion than those in the ALTER0303 trial (53.0% versus 0.7%). To our knowledge, ECOG performance status was confirmed to be an independent prognostic factor to predict the survival among patients with NSCLC.…”
Section: Discussionmentioning
confidence: 76%
“…To our knowledge, management of the patients and adherence of the therapy in a retrospective study was not sufficient and normative compared with the well-designed phase III clinical trial, which was proved in another retrospective study. 28 A third reason could be attributed to the fact that patients with ECOG 2 score in our study accounted for a much higher proportion than those in the ALTER0303 trial (53.0% versus 0.7%). To our knowledge, ECOG performance status was confirmed to be an independent prognostic factor to predict the survival among patients with NSCLC.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, our study was designed as a retrospective analysis. Management of the patients in the retrospective study was not sufficient and normative compared with a well-designed clinical trial, thus deteriorating the efficacy and prognosis in our study to some extent, which was also proved by the previous retrospective study among patients with advanced NSCLC [30]. e above three aspects might be the potential reasons why the median PFS in our study is inferior to that in the Keynote-010 study.…”
Section: Discussionmentioning
confidence: 57%
“…This gene encodes PD-L1, which is an immune inhibitory receptor ligand that is expressed by hematopoietic and non-hematopoietic cells, such as T cells and B cells and various types of tumor cells (25). Hu et al reported that in advanced non-small cell lung cancer (NSCLC) patients receiving apatinib treatment, patients with TT(AA) genotype of CD274:rs2297136 had a significantly longer median PFS and OS than patients with any C(G) allele (26). As apatinib is also an antiangiogenic drug, our study and theirs both support the link between AA genotype of CD274:rs2297136 and a favor response to antiangiogenic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al. reported that in advanced non-small cell lung cancer (NSCLC) patients receiving apatinib treatment, patients with TT(AA) genotype of CD274 :rs2297136 had a significantly longer median PFS and OS than patients with any C(G) allele ( 26 ). As apatinib is also an antiangiogenic drug, our study and theirs both support the link between AA genotype of CD274 :rs2297136 and a favor response to antiangiogenic therapy.…”
Section: Discussionmentioning
confidence: 99%